2022
DOI: 10.15439/2022f162
|View full text |Cite
|
Sign up to set email alerts
|

Information security management in German local government

Abstract: 4The growing importance of information security in organizations is undisputed. This is particularly true of local governments, because modern administrative action is no longer conceivable today without electronic communication media and IT procedures. The complexity of information technology, the increasing degree of networking (also with citizens) and the dependence of the administration on ITsupported procedures has led to the fact that the security of information technology and associated processes must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…As a result, it was found that a significant improvement was achieved for all of them. The detailed results are published in [4] [12, p. 656].…”
Section: Problem Investigation and Relevancementioning
confidence: 99%
See 3 more Smart Citations
“…As a result, it was found that a significant improvement was achieved for all of them. The detailed results are published in [4] [12, p. 656].…”
Section: Problem Investigation and Relevancementioning
confidence: 99%
“…Obtaining Information on Cyber Topics (OSINT) [44], [45], [26] 30. Government Interest [4] 31. Communication [16] 32.…”
Section: Definition Of Measures and Theirmentioning
confidence: 99%
See 2 more Smart Citations